UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI PESERTA DIDIK YANG BERPACARAN DI SEKOLAH MELALUI LAYANAN KONSELING PERORANGAN DI MAS TI BATANG KABUNG PADANG - OKTARINA, YAYUK - (Bimbingan dan Konseling, 2014)
This research was motivated by the presence of the students who dates at school that gave thenegative impact. The role of the counselor at school was very needed toresolved that problem. Thepurpose of this research was to determine the efforts of the counselor to resolved the problem ofstudents who dates at school. The research used descriptive qualitative approach that describes thesymptoms, facts and reality in the field about the efforts of the counselortoresolved the learners whoare dating at school appropriate with situation that researcher found. The informan of this researchwere the counselorand the learners. The instrument that used by researcher was interview guides anddocumentation studies. The technique that researcher used in the processing data through datareduction, data presentation and data conclusion. The result of the research revealed that thecounselorhad a problem in implementing individual counseling services. Based on the result of theresearch recommended to the counselorand the catched of the party to create a conducive environmentfor the learners.